PENDIDIKAN HOLISTIK BERBASIS KULTUR SEKOLAH DALAM MENINGKATKAN KETAATAN BERAGAMA PESERTA DIDIK DI SEKOLAH - Aulia, Aninda Nurul; Fadhilah, Iman; Imroni, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
A positive school culture can help students develop strong personal values such as honesty, discipline, and work ethic. Therefore, to meet the needs of modern education, thorough research on these elements is crucial. However, many schools in Indonesia still struggle to build a culture that supports learning and builds student character. This problem is often caused by poor school management, lack of community support, and a lack of innovation in learning. This study emphasizes the importance of school culture in shaping students' awareness in terms of knowledge, spirituality, and morals. Based on the research results, it can be concluded that holistic education can be implemented by carrying out routine activities or habits, designing school discipline that is aligned with the goals of holistic education, a school culture approach, and instilling the core values of character-strengthening education outside the classroom and extracurricular activities. Educators act as role models, and religious activities such as group prayer and Quran recitation become routine character-building activities. Holistic education based on school culture can increase students' religious awareness and foster responsibility, social awareness, religious discipline, and social awareness. Simply put, a religious school environment has a significant contribution in the formation of students' spirituality or obedience holistically.